Strategi Pemasaran Jasa Pendidikan Di SD Islam Al Azhar 5 Kemandoran Dalam Meningkatkan Jumlah Siswa 2025/2026 - Khansa Aurellia Mantofani; Suparman (JAMBIS : Jurnal Administrasi Bisnis, 2026)
Abstract. The background of this study stems from the phenomenon of increasing competition among private elementary schools in the Jakarta area, as well as changes in parental behavior, which has become more selective and increasingly reliant on digital media such as Instagram, YouTube, and school websites when choosing educational institutions for their children. This phenomenon has prompted schools to not only focus on educational quality but also on marketing strategies that effectively highlight the school's strengths. This study used a descriptive qualitative approach, data collecting technique used such as in-depth interviews, observations, and documentation involving eight informants, including school principals, teachers, administrative staff, parents, and school committee members. This study aimed to analyze the educational service marketing strategies implemented by SD Islam Al Azhar 5 Kemandoran to increase the number of students in the 2025/2026 academic year. The results of the study indicated that the educational service marketing strategy using the 7P marketing mix approach (Product, Price, Place, Promotion, People, Process, Physical Evidence) has been well implemented by SD Islam Al Azhar 5 Kemandoran. These strategies included offering superior educational programs, utilizing social media as a promotional tool, providing communicative services, and managing facilities that support the learning process. The implementation of these strategies has had a positive impact on increasing the number of applicants and new students. The success indicators of this strategy can be seen in terms of educational quality, innovation in the learning process, the school's positive image in the community, the availability of facilities and infrastructure, as well as the professionalism of educators and educational staff. Keywords: Marketing Strategy, Educational Services, 7P Marketing Mix, SD Islam Al Azhar 5 Kemandoran